2022
DOI: 10.3390/healthcare10071353
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Daughters with Anorexia Nervosa: A Qualitative Study on Parents’ Representation of the Problem and Management of the Disorder

Abstract: Background: This study explores the implicit theories by which primary caregivers (PC) of patients diagnosed with anorexia nervosa (AN) understand the eating disorder and interpret their role in treating and managing the problem. Methodology: In-depth, semi-structured, and open interview questions were used to achieve the study’s goals. In total, 19 caregivers, 16 mothers, and three fathers (mean age: 50.74; SD: 5.248) from a public service for the treatment of behavioral disorders in southern Italy were inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Although female subjects scored higher on average than males, they reported greater life satisfaction in general. From the analysis of the scienti c literature, numerous studies have revealed gender differences in caregiving (Carpinelli & Watzlawik, 2023;Carpinelli et al, 2022;Marinaci et al, 2021). Speci cally, activations of caregiving bonds have emerged in female caregivers compared to male caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Although female subjects scored higher on average than males, they reported greater life satisfaction in general. From the analysis of the scienti c literature, numerous studies have revealed gender differences in caregiving (Carpinelli & Watzlawik, 2023;Carpinelli et al, 2022;Marinaci et al, 2021). Speci cally, activations of caregiving bonds have emerged in female caregivers compared to male caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Although female subjects scored higher on average than males, they reported greater life satisfaction, in general. From the analysis of the scientific literature, numerous studies have revealed gender differences in caregiving (Carpinelli & Watzlawik, 2023;Carpinelli et al, 2022;Marinaci et al, 2021). Specifically, activations of caregiving bonds have emerged in female caregivers compared to male caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In remarks to interviewers, these parents described how they were facing a "dreadful monster" and a "living nightmare" [22]. Existing qualitative 3 of 12 findings from interview studies with parents showed that despite their struggles, parents developed sophisticated explanations about their child's eating disorder [23].…”
Section: Introductionmentioning
confidence: 99%